A path analysis of the relation between study habit and students’ academic achievement - Erik Prasetyo; Saiful Ridlo; Nugroho Edi Kartijono (University of Muhammadiyah Malang, 2019)
Study habit (attending lectures, reading books, visiting library, and facing examination) plays an important role in determining academic achievement. The objectives of this study were to analyze the correlation between study habits and academic achievement and analyze the indicators that were most significantly correlated with students’ academic achievement. The study was conducted at the Biology Department of FMIPA UNNES in February - March 2018. The sample of respondents consisted of students of the Biology Department of academic years 2014, 2015 and 2016. A total of 308 students were taken as the sample using proportional stratified random sampling technique. The data was taken using a questionnaire instrument and analyzed using the path analysis method assisted by SmartPLS. The results of the data analysis showed that the indicators of study habit have a significant correlation to the students’ academic achievement of Biology Department. The correlation coefficient values of study habit indicators from high to low were reading books, attending lectures, facing exams, and visiting the library. This study showed that the habit of reading books had the most significant correlation. It is suggested to conduct the experimental research which is related to the effectiveness of reading habit.